Upaya Meningkatkan Hasil Belajar Siswa Materi Surat Al-Ma’un Melalui Model Pembelajaran Problem Based Learning - Ilmeri (MGMP PAI SMP BINTAN, 2023)
Through the application of the PBL learning model with Al Ma'un letter material in class V of SD Negeri 002 Toapaya, Bintan Regency. The subjects of this classroom action research were 19 class V students of SD Negeri 002 Toapaya, Toapaya District, consisting of 13 men and 6 women who came from different backgrounds. The research used in this report is Classroom Action Research. The learning outcomes of class V students at SD Negeri 002 Toapaya can be improved through the PBL learning model. From the research results, the researchers concluded that the use of the Problem Based Learning (PBL) learning model can improve student learning outcomes. This is proven by the evaluation data showing an increase in grades and an increase in the percentage of classical completion.